2010
DOI: 10.1128/aem.02993-09
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Denitrifier Abundance, Denitrification Gene mRNA Levels, Nitrous Oxide Emissions, and Denitrification in Anoxic Soil Microcosms Amended with Glucose and Plant Residues

Abstract: In agricultural cropping systems, crop residues are sources of organic carbon (C), an important factor influencing denitrification. The effects of red clover, soybean, and barley plant residues and of glucose on denitrifier abundance, denitrification gene mRNA levels, nitrous oxide (N 2 O) emissions, and denitrification rates were quantified in anoxic soil microcosms for 72 h. nosZ gene abundances and mRNA levels significantly increased in response to all organic carbon treatments over time. In contrast, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
123
5
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(144 citation statements)
references
References 41 publications
11
123
5
4
Order By: Relevance
“…Numerous studies have examined the factors that influence different pathways involved in denitrification, such as nitrate (Magalhães et al 2005), carbon availability (Henderson et al 2010), pH (Liu et al 2010), and copper concentration (Magalhães et al 2011;Felgate et al 2012). Nevertheless, compaction, as a physical factor, has not received as much attention as the above chemical factors associated with denitrification.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the factors that influence different pathways involved in denitrification, such as nitrate (Magalhães et al 2005), carbon availability (Henderson et al 2010), pH (Liu et al 2010), and copper concentration (Magalhães et al 2011;Felgate et al 2012). Nevertheless, compaction, as a physical factor, has not received as much attention as the above chemical factors associated with denitrification.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that denitrifying communities are affected by soil conditions including temperature, moisture, pH and substrate (e.g. NO 3 À , organic carbon) concentration (Braker et al, 2010;Henderson et al, 2010;Liu et al, 2010;Stres et al, 2008;Lalisse-Grundmann et al, 1988;Renner and Becker, 1970). High exposures to metals such as cadmium, copper, zinc and silver can also be detrimental to denitrifying communities (Holtan-Hartwig et al, 2002;McKenney and Vriesacker, 1985;Throbäck et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Key microbial processes within the soil N cycle are catalyzed by key enzymes, including amoA gene encoding a subunit of ammonia monooxygenase in nitrification, as well as nirS and nirK gene (nitrite reductases) and nosZ gene (nitrous oxide (N 2 O) reductase) involved in denitrification. The diversity and abundance of microorganisms carrying these genes and the actual link to N 2 O emission have been extensively studied in diverse soil ecosystems (for example, Henderson et al, 2010, Leininger et al, 2006Philippot et al, 2006).…”
Section: Introductionmentioning
confidence: 99%